(untitled) (Baghdad Science Journal, 2019)
Tow simple, rapid and sensitive spectrophotometric methods for the determination of mesalazine in pharmaceutical preparations have been carried out. The proposed methods depend on oxidative coupling reaction of mesalazine with m-aminophenol in the existence of N-bromosuccinamide in alkaline medium (method A) and 2,6-dihydroxybenzoic acid in the existence of sodium metaperiodate in basic medium (method B) to produce colored products , show highest absorptions at 640 (nm) and 515 (nm), alternately. Beer’s law was consistent in concentrations extent of 1.25-30 and 0.5-12.5 (µg.mL-1) with molar absorptivity of 0.36×104 and 0.77×104 L.mol-1.cm-1, alternately. The limits of detection (LOD) were 0.0144 and 0.0829 µg.mL-1, while limits of quantitation (LOQ) were 0.0483 and 0.2766 (µg.mL-1), alternately. The suggested methods have been applied successfully to the determination of mesalazine in its pharmaceutical preparations as tablets and suppositories.